Beckman Type 945 Lead Terminator - Beckman Instruments Photographic Services Section (1968)
This instrument was designed to be incorporated into electroencephalograph units and included an impedance meter. An electroencephalogram test detects electrical impulses in the brain via electrodes attached to the scalp.
Keywords: Scientific apparatus and instruments; Electroencephalography; Medical electronics; Beckman Instruments, Inc.